The history of brucellosis in the Middle East: insights for contemporary health challenges - Dadar, Maryam; Bendrey, Robin; Taylor, G. Michael; Shahali, Youcef (Frontiers in Microbiology, 2025)
Brucellosis, a significant zoonotic disease in the Middle East, presents substantial economic and public health consequences. Despite concerted efforts toward its control and eradication, managing the disease faces various challenges. While One Health approaches prioritize interdisciplinary actions to enhance disease understanding, communication, and policy, they often overlook historical perspectives. These regions experience significant brucellosis loads attributed to livestock density, pastoralism, and transboundary animal migration. Historical documentation, encompassing old medical manuscripts, indicates potential early hints of brucellosis-like diseases. The primary Brucella species circulating in the Middle East include Brucella abortus, Brucella melitensis, and Brucella suis, with B. melitensis most commonly associated with human brucellosis. Political and social instability, insufficient finances for disease control programs, and gaps in diagnostic and monitoring infrastructure all provide difficulties for Middle Eastern governments trying to control brucellosis. Although vaccination strategies have been successful, logistical issues have caused inconsistent application. Reducing the spread of the disease depends critically on extra-preventative actions, including public awareness campaigns, controlled cattle trading, and biosecurity enforcement. This study underscores the significance of exploring the rich historical evidence and knowledge of brucellosis, emphasizing its potential contributions to public education, policy development, and improved health outcomes.